2020
DOI: 10.1177/1457496919900414
|View full text |Cite
|
Sign up to set email alerts
|

Branch Duct Intraductal Papillary Mucinous Neoplasms: Recommendations for Follow-Up and Surgery

Abstract: Background and Aims: Pancreatic cysts are increasingly diagnosed, mainly during abdominal imaging performed for other reasons. Between pancreatic cystic neoplasm, intraductal papillary mucinous neoplasms are the most common pre-malignant entities. Intraductal papillary mucinous neoplasms involving side branches overall harbor a low risk of malignancy, and in the recent past, a progressively more conservative approach has been consolidated. Purpose of this report is to summarize the evidence supporting the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 68 publications
0
8
1
Order By: Relevance
“…The incidence of malignant BD-IPMNs and invasive carcinoma are 10.3% and 5.2% in our population which is lower than that in MPD involved IPMNs. Previous studies also indicated that the risk of cancer in BD-IPMNs is low (1%–2%) [ 6 , 19 ] which was slightly lower than our data. High risk malignant IPMNs (18%) or invasive carcinoma (7.5%) was also reported in several studies.…”
Section: Discussioncontrasting
confidence: 86%
“…The incidence of malignant BD-IPMNs and invasive carcinoma are 10.3% and 5.2% in our population which is lower than that in MPD involved IPMNs. Previous studies also indicated that the risk of cancer in BD-IPMNs is low (1%–2%) [ 6 , 19 ] which was slightly lower than our data. High risk malignant IPMNs (18%) or invasive carcinoma (7.5%) was also reported in several studies.…”
Section: Discussioncontrasting
confidence: 86%
“…Little evidence exists in the literature to guide the frequency, duration, and type of surveillance for IPMNs. 1,8 In 2015, American Gastroenterological Association (AGA) guidelines advocated for ceasing surveillance after BD-IPMN patients remained asymptomatic for 5 years. 9 By contrast, European guidelines recommend lifelong surveillance of patients fit for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, the growing amount of IPMN patients under surveillance requires identifying a subpopulation of patients that are at the lowest risk of developing malignancy and who thus do not need annual follow-up. 8 In 2020, Ciprani et al demonstrated that cysts <15 mm at the time of diagnosis had a very low risk of malignant transformation, with that risk decreasing over time. 10 Furthermore, they argued that a size increase of ⩾2.5 mm/year represents the strongest predictor of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the existence of expert consensus policies 1–3 regarding the management of pancreatic cystic neoplasms (PCNs) for more than a decade, the lack of data on guidelines application in the real word is a matter of concern 4,5 . If guidelines are not enforced in clinical practice, this can result in serious inequalities in terms of PCNs' management.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the existence of expert consensus policies 1 , 2 , 3 regarding the management of pancreatic cystic neoplasms (PCNs) for more than a decade, the lack of data on guidelines application in the real word is a matter of concern. 4 , 5 If guidelines are not enforced in clinical practice, this can result in serious inequalities in terms of PCNs' management. Indeed, whereas most practitioners dealing with PCNs allege to know the available guidelines for their clinical practice, 6 which guidelines are chosen in specific clinical scenarios is yet unknown.…”
Section: Introductionmentioning
confidence: 99%